Flipped learning and its challenges: understanding students' struggles in Indonesian EFL contexts from teachers' viewpoint - Pilu, Reski; Jabu, Baso; Sulaiman, Iskandar (Frontiers in Education, 2025)
This study examines the challenges students face in flipped learning in Indonesian English as a Foreign Language (EFL) classrooms from teachers' perspectives. Flipped learning shifts content delivery outside the classroom and prioritizes active learning in class, but its implementation presents difficulties, particularly in EFL settings. Fifteen experienced teachers from one of the private university's English Study Programs in South Sulawesi, Indonesia, were interviewed. Thematic analysis identified key student challenges, including difficulties with time management and self-regulation, unequal access to technology and reliable internet, reluctance to participate actively in class, struggles with independent content comprehension, and challenges in adapting to the demands of the flipped model. Some students also experienced feelings of isolation due to reduced social interaction. These findings underscore the importance of educators providing explicit self-regulation strategies, ensuring equitable access to technology, fostering interactive classroom environments, and designing collaborative activities that promote student engagement. This study offers practical insights for improving flipped learning in EFL classrooms.